The Mandate of Charitable Organizations to Engage in Businesses as Income Generation Activity: Theories, International Experiences and Ethiopian Law - Abate, Yibekal (Bahir Dar University Journal of Law, 2022)
The engagement of charitable organizations in business, as income generating activity, is a contentious subject. Those supporting charity trading see it as a venue of financial support for the missions of charities while others are against this move arguing that charity trading will degrade the defining virtues of charities – namely, that they operate outside of the for-profit marketplace. Theoretically, there are different lines of thought with regards to charity trading such as exclusivity doctrine, the doctrine of primary purpose trading, doctrine of ancillary trading, and the doctrine of non-primary purpose or unrelated trading. Countries adopt one or two of these theories and largely they view income generation activities from different perspectives– its relation with the primary purpose of the charity, asset protection of charities (the risk of business failure), and its effect on market competition. The Organization of Civil Societies Proclamation (OCS) of Ethiopia allows charities to engage in any lawful business activity without a condition of the element of relatedness to the mission of the charity and other concerns. Generally, there are doubts about the legitimacy and extent of engagement of charities in business. This article examines whether and to what extent, charities shall be allowed to engage in business activities. Following doctrinal research methodology, the article critically examined the theories, international practices, empirical evidences and legislations of non-profit organizations. Based on the analysis made the article concludes that as charities are inherently formed to pursue charitable purposes and since business activities as a secondary mission may distract them away from their central missions, their engagement in trade activities shall be limited only to charity purpose-related trading. Thus, the OCS law of Ethiopia needs to be re-visited in light of the foundational theories of the non-profit sector and major international experiences.